Analisis Program Pelatihan dan Budaya Organisasi dalam Meningkatkan Kinerja Karyawan pada PT Bufa Aneka - Adiyatul Fahri; Siti Kholifah (MANAJEMEN, 2026)
The purpose of this study is to analyze the influence of training and organizational culture on employee  performance at PT Bufa Aneka. The study used an associative quantitative method with a population of 91 employees. The sampling technique used simple random sampling with a total of 74 respondents. Data were collected through questionnaires and analyzed using multiple linear regression analysis with the help of SPSS version 25. The results of the study indicate that: (1) training has a positive and significant effect on employee performance (t count = 2.015; sig. = 0.048), (2) organizational culture has a positive and significant effect on employee performance (t count = 3.684; sig. = 0.000), and (3) training and organizational culture simultaneously have a significant effect on employee performance (F count = 11.586; sig. = 0.000). The coefficient of determination value of 22.5% indicates that both variables contribute to improving employee performance. Thus, increasing the effectiveness of training and strengthening organizational culture are important strategies to optimize employee performance at PT Bufa Aneka.